2016
DOI: 10.3389/fphar.2016.00083
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic β Cell Mass Death

Abstract: Type two diabetes (T2D) is a challenging metabolic disorder for which a cure has not yet been found. Its etiology is associated with several phenomena, including significant loss of insulin-producing, beta cell (β cell) mass via progressive programmed cell death and disrupted cellular autophagy. In diabetes, the etiology of β cell death and the role of mitochondria are complex and involve several layers of mechanisms. Understanding the dynamics of those mechanisms could permit researchers to develop an interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 174 publications
(168 reference statements)
3
43
0
Order By: Relevance
“…This finding is interesting because hyperglycaemia is generally associated with beta cell death. In contrast, in the presence of lipotoxicity, beta cell proliferation is suppressed in the co‐culture system similar to previous studies (Marrif & Al‐Sunousi, ). All these findings suggest that PI‐MSCs direct beta cells to proliferation in the presence of glucose.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is interesting because hyperglycaemia is generally associated with beta cell death. In contrast, in the presence of lipotoxicity, beta cell proliferation is suppressed in the co‐culture system similar to previous studies (Marrif & Al‐Sunousi, ). All these findings suggest that PI‐MSCs direct beta cells to proliferation in the presence of glucose.…”
Section: Discussionsupporting
confidence: 89%
“…C-peptide and insulin levels were decreased significantly in diabetes rats. This might be due to the destruction of pancreatic β-cells and thereby induces hyperglycemia [52]. In the present study the significant increase in the levels of insulin and C-peptide was observed in SGP administrated diabetic rats ( Figure 5).…”
Section: Discussionsupporting
confidence: 55%
“…T2D progression through impaired pancreatic beta cells function and development of insulin resistance has been associated with autophagy [125–128]. Upon insulin resistance, pancreatic cells enhance their insulin secretion (hyperinsulinemia) to compensate for hyperglycemia on the early onset of T2D (Fig.…”
Section: Autophagy and Type 2 Diabetes (T2d)mentioning
confidence: 99%